Preserving choice in breast cancer treatment: A different perspective on contralateral prophylactic mastectomy - Kelly Pender; Daleela Dodge; Jessica M Collins (Women's Health, 2023)
Contralateral prophylactic mastectomy is the removal of both breasts when only one is affected by cancer. Rates of this controversial cancer treatment have been increasing since the late 1990s, even among women who do not have the kind of family history or known genetic mutation that would put them at high-risk for another breast cancer. Citing contralateral prophylactic mastectomy’s lack of oncologic benefit and increased risk of surgical complications, the American Society of Breast Surgeons discourages contralateral prophylactic mastectomy for average-risk women with unilateral cancer, as does most of the medical literature on this topic. Within this literature, desire for contralateral prophylactic mastectomy is often painted as the product of an emotional overreaction to a cancer diagnosis and misunderstanding of breast cancer risk. Drawing on the personal experience of a breast cancer survivor, as well as relevant medical literature on breast cancer screening and surgery, this article offers a different perspective on the ongoing popularity of contralateral prophylactic mastectomy, one that focuses on practical experiences and logical deliberations about those experiences. Specifically, it calls attention to two features of the contralateral prophylactic mastectomy decision-making situation that have been inadequately covered in the medical literature: (1) the way that breast cancer screening after a breast cancer diagnosis can become a kind of radiological overtreatment, even for “average-risk” women; and (2) how desire for bodily symmetry after breast cancer, which can best be achieved through bilateral reconstruction or no reconstruction, drives interest in contralateral prophylactic mastectomy. The goal of this article is not to suggest that all women who want contralateral prophylactic mastectomy should have the surgery. In some cases, it is not advisable. But many “average-risk” women with unilateral cancer have good reasons for wanting contralateral prophylactic mastectomy, and we believe their right to choose it should be protected.